2020
DOI: 10.1001/jamainternmed.2020.4624
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Against SARS-CoV-2—Important Questions, Unclear Answers

Abstract: A, et al. Evaluating the association of clinical characteristics with neutralizing antibody levels in patients who have recovered from mild COVID-19 in Shanghai, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The observed waning nAb does not mean that individuals lose their immune status or are susceptible to future re‐infections; only their level is below the defined cut‐off for donation. Even if nAb becomes undetectable in the future, it is likely that in re‐exposure, both the memory and killer T cells will be engaged in secondary immunologic response 32,45 . It is possible that CCP individuals presenting low nAb titers have recovered due to additional/complementary immune mechanisms (T‐cell response, cytokines) other than classical humoral response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed waning nAb does not mean that individuals lose their immune status or are susceptible to future re‐infections; only their level is below the defined cut‐off for donation. Even if nAb becomes undetectable in the future, it is likely that in re‐exposure, both the memory and killer T cells will be engaged in secondary immunologic response 32,45 . It is possible that CCP individuals presenting low nAb titers have recovered due to additional/complementary immune mechanisms (T‐cell response, cytokines) other than classical humoral response.…”
Section: Discussionmentioning
confidence: 99%
“…Even if nAb becomes undetectable in the future, it is likely that in re-exposure, both the memory and killer T cells will be engaged in secondary immunologic response. 32,45 It is possible that CCP individuals presenting low nAb titers have recovered due to additional/complementary immune mechanisms (T-cell response, cytokines) other than classical humoral response. Studies have demonstrated that SARS-CoV-2 re-infection in previously immune animals was capable of inducing a robust protective immune response, 37,40,46 showing that immunity is maintained and protective in subsequent exposures, although human protection might last for only a period of 1-2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Ab-based therapeutics directed against SARS-CoV-2 still present lights and shadows 14 . Preclinical data and phase-III clinical studies indicate that mAbs could be effectively deployed for prevention or treatment during the viral symptoms phase of the disease 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The waning nAb levels observed in this study does not mean that these individuals lost their immune status or will be susceptible to re-infections in the future, as they markedly are nAb producers; only their level is below a pre-defined cut-off for donation. Even if their nAb becomes undetectable in the future, it is likely that in re-exposure, both the memory and killer T-cells will be engaged in a secondary immunologic response 24, 46 . It is possible that CCP individuals who already presented with low nAb titers could have recovered due to additional/complementary immune mechanisms (T-cell response, cytokines, etc.)…”
Section: Discussionmentioning
confidence: 99%